Consumer willingness to pay for shelf life of high-temperature, short-time-pasteurized fluid milk: Implications for smart labeling and food waste reduction - P. Endara; M. Wiedmann; A. Adalja (Journal of Dairy Science, 2023)
ABSTRACT: Food waste in the United States was valued at $285 billion in 2019, representing 70% of all food surplus; dairy and eggs alone represented 15.90% of food surplus. Milk is the fifth most consumed beverage in the United States, and therefore its contribution to food waste has significant economic and environmental ramifications. Smart labels that provide precise spoilage information for fluid milk may help reduce food waste in fluid milk, but it is unclear if consumers will accept or pay for this novel technology. This paper examines consumer preferences for high temperature, short time pasteurized fluid milk shelf life and smart date labels and tests how information about the environmental impact of fluid milk food waste affects consumers' acceptance and willingness to pay. We used a choice-based conjoint study administered in an online survey, along with a between-subject experiment to measure preferences under different information treatments about the environmental impact of food waste. Our results suggest that consumers' valuations of extended shelf life and an ecolabel is positive; however, using the smart label creates disutility for consumers, thereby hindering acceptance of new labeling technology that may facilitate food waste reduction in the milk industry. These findings imply that retailers should find alternative means to enhance the communication of precise shelf life information and its role in reducing food waste.